2014
DOI: 10.1186/1471-2318-14-8
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in adiponectin levels and body composition in older adults: Hallym aging study

Abstract: BackgroundBody composition changes with ageing can influence the adiponectin concentration. However, the component of body composition that is associated with adiponectin concentrations in older adults remains unclear.MethodsThere were 152 males and 168 females aged 65 years or older that participated in the 2010 Hallym Aging Study (HAS). Body composition (assessed by dual energy X-ray absorptiometry; DXA), anthropometric parameters and adiponectin were obtained from all participants. Multivariate linear regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 35 publications
3
36
1
Order By: Relevance
“…Previous work in the cardiovascular field supports our finding that peripheral CRP (Cartier et al, 2009; Khera et al, 2005; Lakoski et al, 2006; McConnell et al, 2002; Wener et al, 2000;), leptin (Couillard et al, 1997; Hellström et al, 2000; Hickey et al, 1996; Kennedy et al, 1997; Ostlund et al, 1996), and adiponectin levels (Böttner et al, 2004; Saltevo et al, 2009; Song et al, 2014) are naturally higher in women compared to men, independent of age, race, and body mass index. Our study expands these findings in demonstrating that other inflammatory markers, such as TNF, are also higher in women than in men.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous work in the cardiovascular field supports our finding that peripheral CRP (Cartier et al, 2009; Khera et al, 2005; Lakoski et al, 2006; McConnell et al, 2002; Wener et al, 2000;), leptin (Couillard et al, 1997; Hellström et al, 2000; Hickey et al, 1996; Kennedy et al, 1997; Ostlund et al, 1996), and adiponectin levels (Böttner et al, 2004; Saltevo et al, 2009; Song et al, 2014) are naturally higher in women compared to men, independent of age, race, and body mass index. Our study expands these findings in demonstrating that other inflammatory markers, such as TNF, are also higher in women than in men.…”
Section: Discussionsupporting
confidence: 88%
“…In healthy individuals, it has been demonstrated that peripheral levels of CRP (Cartier et al, 2009; Khera et al, 2005; Lakoski et al, 2006; McConnell et al, 2002, Wener et al, 2000), leptin (Couillard et al, 1997, Hellström et al, 2000; Hickey et al, 1996; Kennedy et al, 1997; Ostlund et al, 1996), and adiponectin (Böttner et al, 2004; Saltevo et al, 2009; Song et al, 2014) are naturally higher in women compared to men, independent of age, race, and body mass index. Despite this, although most studies of sleep apneics statistically control for gender in their analyses, very few have expressly investigated possible gender differences in inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In older populations, a higher adiponectin concentration was associated with a greater risk of cardiovascular disease, stroke and mortality. However, other authors have found no association between adiponectin and the risk of stroke [46] . Leptin is an adipokine that is now considered to control lipoprotein function, acute phase reactants, glucocorticoid metabolism, inflammation, immune function and reproduction and, hence, is key to integrating adipose tissue with competing biological functions [47] .…”
Section: Acta Pharmacologica Sinica Npgmentioning
confidence: 94%
“…Changes in RBC counts, Hb levels, and hematocrit (Hct) levels (erythroid-related variables) were compared between each group and each subgroup. We performed all analyses on the basis of sex, owing to physiological sex-related differences [1,22]; RBC counts, Hb levels, and Hct levels are significantly higher in men than in women, whereas adiponectin levels are significantly lower.…”
Section: Methodsmentioning
confidence: 99%